Hydroclimatic change challenges the EU planned transition to a carbon neutral electricity system. (21st September 2021) - Carlino, Angelo; De Vita, Alessia; Giuliani, Matteo; Zamberletti, Patrizia; Capros, Pantelis; Recanati, Francesca; Kannavou, Maria; Castelletti, Andrea
Abstract: EU Member States are progressively decarbonizing their electricity systems by replacing fossil fuels with renewable sources to achieve rapid greenhouse gases emissions reductions. While the planned decarbonized system will be more resilient to hydroclimatic change than existing water-dependent portfolios, water availability and temperature are still influential factors during this transition to a carbon neutral electricity system, with potential negative impacts on the economy and the environment. Here, we conduct a model-based analysis to assess the impacts of hydroclimatic change on EU decarbonization strategies in two regions, the Iberian Peninsula (IP) and the Danube river basin, characterized by a high share of water-dependent energy sources and expected to be highly affected by climate change. We find that, under the reference electricity system scenario for 2040 aligned with the EU climate and energy strategies, generation from fossil fuels increases, in particular from combined cycle gas turbine plants, to balance the reduction of hydro generation consistently observed in the hydroclimatic scenarios examined. This reduction, in conjunction with increased thermal plants shutdown events due to high water temperature especially in the IP, produces load cuts undermining the reliability of the electricity system. Moreover, increased fossil fuel use results in higher generation costs and carbon intensity, jeopardizing emissions reduction targets and ultimately slowing down the decarbonization process.